A systematic approach to the hydraulic and structural principles involved in the design of low-head radial gate - Lin, Kuo-chang, author; Lewis, Robert L., advisor; Christensen, N. A. (Nephi Albert), 1903-, committee member; Clark, Andrew Giles, committee member; Stimmel, L. H., committee member (Colorado State University. Libraries, 1947)
To view the abstract, please see the full text of the document.
Keywords: Hydraulic gates